TEACHERS’ KNOWLEDGE AND BELIEFS REGARDING ONLINE PLATFORMS FOR TEACHING ENGLISH LISTENING: A CASE STUDY AT A UNIVERSITY IN INDONESIA (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2021)
Knowledge and beliefs are two aspects of cognition that play very significant roles in the teaching and learning process. Many studies show that what teachers know and believe has a high impact on their classroom. This study examined university teachers' knowledge and beliefs regarding online platforms in teaching English listening. Using a case study design, we examined two university teachers teaching English listening online. The finding showed that participants' knowledge and beliefs about online platforms for teaching English listening align with their teaching practices. However, the implementation of online platforms was still considered less optimal. Finally, the implications for teacher development are highlighted.